2022
DOI: 10.1556/030.2022.01860
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical outcomes of vaccinated and unvaccinated patients with hospitalization for COVID-19

Abstract: We aimed to compare vaccinated and unvaccinated patients hospitalized with COVID-19 in terms of disease severity, need for intensive care unit (ICU) admission, and death. In addition, we determined the factors affecting the COVID-19 severity in vaccinated patients. Patients aged 18–65 years who were hospitalized for COVID-19 between September and December 2021 were retrospectively analyzed in three groups: unvaccinated, partially vaccinated, and fully vaccinated. A total of 854 patients were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“… 6 In addition, full vaccination reduced the need for ICU admission by 49.7% and mortality by 56.5%. 6 In a retrospective study evaluating 486 hospitalized COVID-19 patients, 4 not having been vaccinated or not having been fully vaccinated were factors associated with increased mortality. In individuals who require hospitalization despite COVID-19 vaccination, the length of hospital stay, the need for ICU admission, and mortality are lower than in unvaccinated individuals.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“… 6 In addition, full vaccination reduced the need for ICU admission by 49.7% and mortality by 56.5%. 6 In a retrospective study evaluating 486 hospitalized COVID-19 patients, 4 not having been vaccinated or not having been fully vaccinated were factors associated with increased mortality. In individuals who require hospitalization despite COVID-19 vaccination, the length of hospital stay, the need for ICU admission, and mortality are lower than in unvaccinated individuals.…”
mentioning
confidence: 99%
“…Studies have shown that vaccination reduces COVID-19 mortality, COVID-19 severity, and the length of hospital stay. 4 , 6 , 7 Individuals with complete vaccination schedules had higher survival rates in a retrospective study evaluating 854 patients with COVID-19. 6 In addition, full vaccination reduced the need for ICU admission by 49.7% and mortality by 56.5%.…”
mentioning
confidence: 99%
See 3 more Smart Citations